Compliance with international financial reporting standards: the case of listed firms in Ghana. Issue 1 (4th July 2016) - Appiah, Kingsley Opoku; Awunyo-Vitor, Dadson; Mireku, Kwame; Ahiagbah, Christian
Abstract : Purpose: This study aims to examine the association between five firm-specific characteristics and the level of compliance with International Financial Reporting Standards (IFRS) by companies listed on Ghana Stock Exchange. The five firm-specific characteristics are firm size, profitability, leverage, auditor type and firm age. Design/methodology/approach: The study uses dataset from 31 listed Ghanaian firms from 2008 to 2012. Random effect is used to examine the influence of the predictive variables on the level of IFRS corporate compliance. Findings: The result reveals a positive significant relationship between the level of compliance and firm size, auditor type, cross-listing and sector (information and communications technology (ICT) and agro-forestry). On the contrary, the level of compliance exhibits a negative significant association with leverage and firm age. It is observed that the level of compliance is not related to profitability. The results are robust to different model specifications. Practical implications: This study identifies firm-specific characteristics that influence IFRS compliance by listed firms in Ghana. This would aid accounting policy makers to institute strategies to encourage compliance with IFRS by the listed firms. Originality/value: The study contributes to financial reporting literature relating to developing economies and Ghana, in particular.